2014
DOI: 10.5897/ijlp12.020
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic characteristics and husbandry practices of cattle breeders in the Vina division, Cameroon

Abstract: In order to assess socio-economic characteristics of cattle breeders and their effect on farmers' practices, a survey was carried out in Vina division within the Adamawa highlands of Cameroon, from November, 2009 to October, 2010. Data were collected from 159 farmers in 9 localities, using a structured questionnaire. Information on breeder's ethnic group, age, marital status, education level, number of children, reasons for rearing cattle, labor distribution, herd size and composition, feeding and reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The number of milking cows in the enterprises were reported as 2 heads in 52.5% of the enterprises in Tanzania (Mzingula, 2019), 1-5 heads in %37.6 of the enterprises in West Kenya (Amimo et al, 2011), 6.7 heads in average in Bangladesh (Datta et al, 2019), and 10-50 heads in more than half (50.7%) of the enterprises in Nigeria (Saleh, 2018). On the other hand, in a study conducted in Cameroon, it was reported that 37.4% of the enterprises had 50-100 cattle (Mingoas Kilekoung et al, 2014). In another study conducted in the Northern Benin province of West Africa, it was determined that the average herd size was 45 heads, but the number of cattle in 41.0% of the enterprises was less than 25 heads (Houessou et al, 2019).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The number of milking cows in the enterprises were reported as 2 heads in 52.5% of the enterprises in Tanzania (Mzingula, 2019), 1-5 heads in %37.6 of the enterprises in West Kenya (Amimo et al, 2011), 6.7 heads in average in Bangladesh (Datta et al, 2019), and 10-50 heads in more than half (50.7%) of the enterprises in Nigeria (Saleh, 2018). On the other hand, in a study conducted in Cameroon, it was reported that 37.4% of the enterprises had 50-100 cattle (Mingoas Kilekoung et al, 2014). In another study conducted in the Northern Benin province of West Africa, it was determined that the average herd size was 45 heads, but the number of cattle in 41.0% of the enterprises was less than 25 heads (Houessou et al, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, the average age of cattle breeders in Azerbaijan and Georgia was reported to be 33.4 and 41.3 years, respectively (Neudert et al, 2020). The average age of breeders was 48 years in Nigeria (Saleh, 2018), 47 years in Finland (Sahlström et al, 2014), while the majority of the cattle breeders (59.1%) in Cameroon was between 26-45 years old (Mingoas Kilekoung et al, 2014). In different studies conducted in Turkey, it was reported that the age of breeders was between 41-47 years (Demir et al, 2014;Bakan and Aydın, 2016;Şahin and Karadağ Gürsoy, 2016;Tapkı et al al., 2018;Mat and Cevger, 2020;Paksoy and Bulut, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Bovine F. gigantica infections have been associated with 22 kg per animal reduction in live-weight gains in yearling cattle [50] and economic losses due to liver condemnations [51]. Poor weight gain has been highlighted as a production-limiting factor in cattle production in Cameroon [52] and could be partly attributed to active F. gigantica infections. Previous abattoir studies have reported higher prevalence in slaughtered cattle in Cameroon (~ 80%) [32, 33, 53].…”
Section: Discussionmentioning
confidence: 99%
“…The main breeds used were local (Gudali) and crossed breeds (Gudali x Holstein) as reported by several authors (Kibwana et al, 2012;Mingoas et al, 2014;Kamga et al, 2001). For local breeds, milk production is estimated at 1.5 to 3 liters per day (Messine et al, 1995).…”
Section: Type III Breedersmentioning
confidence: 99%
“…The present study showed that the foot-and-mouth virus circulated in this part of Cameroon. Mingoas et al (2014) report that foot and mouth (14.5%) is the main disease after trypanosomosis (74.5%). This shows that animal health is not sufficiently under control in sub-Saharan Africa and Cameroon in particular.…”
Section: Type III Breedersmentioning
confidence: 99%